Development Of An Android-Based Arabic Dictionary For Independent Learning Resources In State Islamic Universities - Shodiq, Muhammad Jafar (Ijaz Arabi Journal of Arabic Learning, 2025)
Students often use Google Translate to translate unknown “educational terms”. However, Google Translate is often inaccurate. This study aims to develop an android-based educational terms dictionary application (Mu’jam al-Musṭalahāt al-Tarbawiyah) as an independent learning resource for PTKIN students, to determine its quality, and to determine students’ responses to the dictionary. This study is a development research with a procedural model. The development procedure in this study refers to the development research procedure by Timpus Litjaknov with development steps, namely analysis of the product to be developed, initial product development, expert validation and revision, small-scale field trials and product revisions, large-scale field trials, and the final product. The data analysis techniques used are quantitative and qualitative data. The results of this research are: 1) The Android-based Mu'jam al-Musṭalahāt al-Tarbawiyah dictionary has been successfully developed as an independent learning resource for students of state Islamic universities with the name of a trilingual educational terms dictionary, 2) Based on the assessment of media experts, the Mu'jam al-Musalahāt al-Tarbawiyah dictionary has very good quality with an average score of 3.50 and based on the media expert's assessment it is 3.50, 3) student response to the application The Mu'jam al-Musṭalahāt al-Tarbawiyah dictionary in small-scale field trials obtained an average score of 3.02, while in large-scale field trials it obtained an average score of 3.30.